Sputum bacterial load and bacterial composition correlate with lung function and are altered by long-term azithromycin treatment in children with HIV-associated chronic lung disease - Regina E. Abotsi; Felix S. Dube; Andrea M. Rehman; Shantelle Claassen-Weitz; Yao Xia; Victoria Simms; Kilaza S. Mwaikono; Sugnet Gardner-Lubbe; Grace McHugh; Lucky G. Ngwira; Brenda Kwambana-Adams; Robert S. Heyderman; et al. (Microbiome, 2023)
Abstract Background Long-term azithromycin (AZM) treatment reduces the frequency of acute respiratory exacerbation in children and adolescents with HIV-associated chronic lung disease (HCLD). However, the impact of this treatment on the respiratory bacteriome is unknown. Method African children with HCLD (defined as forced expiratory volume in 1 s z-score (FEV1z) less than − 1.0 with no reversibility) were enrolled in a placebo-controlled trial of once-weekly AZM given for 48-weeks (BREATHE trial). Sputum samples were collected at baseline, 48 weeks (end of treatment) and 72 weeks (6 months post-intervention in participants who reached this timepoint before trial conclusion). Sputum bacterial load and bacteriome profiles were determined using 16S rRNA gene qPCR and V4 region amplicon sequencing, respectively. The primary outcomes were within-participant and within-arm (AZM vs placebo) changes in the sputum bacteriome measured across baseline, 48 weeks and 72 weeks. Associations between clinical or socio-demographic factors and bacteriome profiles were also assessed using linear regression. Results In total, 347 participants (median age: 15.3 years, interquartile range [12.7–17.7]) were enrolled and randomised to AZM (173) or placebo (174). After 48 weeks, participants in the AZM arm had reduced sputum bacterial load vs placebo arm (16S rRNA copies/µl in log10, mean difference and 95% confidence interval [CI] of AZM vs placebo − 0.54 [− 0.71; − 0.36]). Shannon alpha diversity remained stable in the AZM arm but declined in the placebo arm between baseline and 48 weeks (3.03 vs. 2.80, p = 0.04, Wilcoxon paired test). Bacterial community structure changed in the AZM arm at 48 weeks compared with baseline (PERMANOVA test p = 0.003) but resolved at 72 weeks. The relative abundances of genera previously associated with HCLD decreased in the AZM arm at 48 weeks compared with baseline, including Haemophilus (17.9% vs. 25.8%, p < 0.05, ANCOM ω = 32) and Moraxella (1% vs. 1.9%, p < 0.05, ANCOM ω = 47). This reduction was sustained at 72 weeks relative to baseline. Lung function (FEV1z) was negatively associated with bacterial load (coefficient, [CI]: − 0.09 [− 0.16; − 0.02]) and positively associated with Shannon diversity (0.19 [0.12; 0.27]). The relative abundance of Neisseria (coefficient, [standard error]: (2.85, [0.7], q = 0.01), and Haemophilus (− 6.1, [1.2], q < 0.001) were positively and negatively associated with FEV1z, respectively. An increase in the relative abundance of Streptococcus from baseline to 48 weeks was associated with improvement in FEV1z (3.2 [1.11], q = 0.01) whilst an increase in Moraxella was associated with decline in FEV1z (-2.74 [0.74], q = 0.002). Conclusions AZM treatment preserved sputum bacterial diversity and reduced the relative abundances of the HCLD-associated genera Haemophilus and Moraxella. These bacteriological effects were associated with improvement in lung function and may account for reduced respiratory exacerbations associated with AZM treatment of children with HCLD. Video Abstract